Physical and optical properties of Dy3+: Li2O-K2O- B2O3 glasses - Azizan, Shaidatul Asrin; Hashim, Suhairul; Razak, Nashru Amira; Abu Mhareb, Mohammad Hasan; Alajerami, Yasser Saleh Mustafa; Tamchek, Nizam (Elsevier, 2014)
The luminescence, lasing and sensing properties of rare earth (RE) ions have drawn much interest among researchers. We have focussed on the physical and optical properties of Li2O–K2O–B2O3 (LKB) with different concentrations of dysprosium (Dy3+) ions. The glass samples were prepared using melt quenching method. The physical parameters of the prepared glass were determined. Optical measurements such as XRD, FTIR, absorption and photoluminescence spectra have been carried out. Dy3+: LKB glass showed eight absorption bands with hypersensitive transition located at 1265 nm (6H15/2 → 6F11/2–6H9/2). Finally, Dy3+: LKB glass exhibited two intense luminescence emission at 481 nm (4F9/2 → 6H15/2; blue) and 573 nm (4F9/2 → 6H13/2; yellow) and feeble band at 683 nm (4F9/2 → 6H11/2; red) with excitation wavelength at 370 nm. The results obtained are prevalent with others studies and also point to its use in solid-state laser, optoelectronic devices and W-LEDs application.